PENGARUH KEPEMILIKAN PUBIK DAN GROWTH OPPORTUNITY TERHADAP KONSERVATISME AKUNTANSI - Rokhmah Agus C (JURNAL EKONOMI, 2020)
The research aimed to knowing influencing of Public Ownership and Growth Opportunity on Acconting Conservatism and to knowing influencing of Public Ownership and Growth Opportunity together on Acconting Conservatism. Data used in this reasearch are Manufacturing Business data in Basic Industry and Chemical Sectors on the Indonesian Stock Exchange. The period of this research is for 3 years, started from 2016 until 2018 for was data of Manufacturing Business in Basic Industry and Chemical sectors on Indonesian Stock Exchange. The sampel selected by purposive sampling method. The type of data used is secondary data and total sample used in this research is 10 companies that have been selected based on predetermined criteria. Methods of data analysis used is multiple linear regression. The results of this research indicate that : 1. Public ownership affect accounting conservatism. 2. Growth opportunity doesn’t affects accounting conservatism. 3. Public ownership and growth opportunity affects accounting conservatism. Further research is recommended that can expand the research sample, add variables and extend the periodde of research. Keywords : Public Ownership, Growth Opportunity, and Accounting Conservatism